Peran Guru PAK Dalam Penanaman Kerohanian Pemuda Kristen Dalam Membangun Hubungan Erat Dengan Tuhan (International Forum of Researchers and Lecturers, 2023)
Youth is when humans are in their twenties. During youth, humans cannot be called adults, but they cannot also be called children. However, as the next generation, some Christian youths do not understand the importance of cultivating spirituality in building a close relationship with God. There are various models that can be implemented nowadays in order to produce young people who build a close relationship with God, one of which is the spiritual cultivation of Christian youth in building a close relationship with God. This learning certainly utilizes various youth spirituality that are relevant in the world of education. The goal is to improve the outcome and quality of their Faith process. The method used in this writing is a qualitative method. Through qualitative methods the authors use library research (library research). Spiritual formation is very important for young Christians. Because youth has a very important role for the growth of the church, and youth is the backbone of the church in carrying out the functions and roles of the church it is very necessary. Therefore the church needs to foster and direct youth. In accordance with God's word in Proverbs 22:6